2006
DOI: 10.1007/s00018-006-6148-x
|View full text |Cite
|
Sign up to set email alerts
|

Espins and the actin cytoskeleton of hair cell stereocilia and sensory cell microvilli

Abstract: The espins are novel actin-bundling proteins that are produced in multiple isoforms from a single gene. They are present at high concentration in the parallel actin bundle of hair cell stereocilia and are the target of deafness mutations in mice and humans. Espins are also enriched in the microvilli of taste receptor cells, solitary chemoreceptor cells, vomeronasal sensory neurons and Merkel cells, suggesting that espins play important roles in the microvillar projections of vertebrate sensory cells. Espins ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 77 publications
(209 reference statements)
1
71
0
Order By: Relevance
“…The actin filament has a versatile structure, and subtle structural changes induced by barbed end-binding regulators may favor the binding of, for example, distinctive bundling proteins, thus further differentiating the function of actin arrays. This might explain why bundling proteins like fascin (37) or espin (38) are found associated with bundles of filaments initiated by different machineries.…”
Section: Insight Into the Mechanism Of Actin-based Motility From Recomentioning
confidence: 99%
“…The actin filament has a versatile structure, and subtle structural changes induced by barbed end-binding regulators may favor the binding of, for example, distinctive bundling proteins, thus further differentiating the function of actin arrays. This might explain why bundling proteins like fascin (37) or espin (38) are found associated with bundles of filaments initiated by different machineries.…”
Section: Insight Into the Mechanism Of Actin-based Motility From Recomentioning
confidence: 99%
“…S1; refs. 4,5). All isoforms of ESPIN encode the same region of a 116-amino acid actin-bundling module (ABM), which is necessary for potent actin-bundling and microvillar parallel actin bundle (PAB) elongating activities (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…4,5). All isoforms of ESPIN encode the same region of a 116-amino acid actin-bundling module (ABM), which is necessary for potent actin-bundling and microvillar parallel actin bundle (PAB) elongating activities (4,5). Mutation in Wiskott-Aldrich syndrome protein homology 2 (WH2) and ABM domains of ESPIN gene causes hereditary deafness and vestibular dysfunction accompanied by stereociliary shortening in jerker mice and humans (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors have been identified that contribute to the length regulation of microvilli or microvillusderived stereocilia and their organization and arrangement on the apical surface of epithelial cells. Many of these factors directly bind to actin in protrusions, either cross-linking actin filaments or linking them to the plasma membrane (reviewed by Lin et al, 2005;Sekerková et al, 2006;Manor and Kachar, 2008;Tepass, 2009;Fehon et al, 2010). In particular, myosin motor proteins, which bind to and travel along actin filaments, control multiple processes in microvilli and stereocilia.…”
Section: Introductionmentioning
confidence: 99%